Interface effects from moisture in nanocomposites of 2D graphene oxide in cellulose nanofiber (CNF) matrix – A molecular dynamics study. Issue 4 (12th January 2022) - Mianehrow, Hanieh; Berglund, Lars A.; Wohlert, Jakob
Abstract : Molecular dynamics (MD) simulation is used to study effects from moisture at cellulose nanofibril (CNF)–graphene oxide (GO) interfaces adhering in the wet state. Abstract : Molecular dynamics (MD) simulation is used to study effects from moisture at cellulose nanofibril (CNF)–graphene oxide (GO) interfaces adhering in the wet state. Two CNF models with different surface chemistry are used: native cellulose nanofibrils (NCNF) and TEMPO-oxidized cellulose nanofibrils (TOCNF). Work of adhesion and interfacial shear strength at the CNF–GO interface is compared with CNF–graphene interfaces to interpret interaction mechanisms. Any trapped interfacial water reduces adhesion strongly. Results show, however, that there is a meta-stable state where water is initially present at the CNF–GO interface but disappears with time to form a dry interface. Once a solvent-excluded interface is formed between CNF and GO, the surface oxidation has little effect on molecular adhesion. We propose that the main adhesion mechanism is entropy gain from release of water molecules as CNF and GO jump into contact when brought close together. Hydrogen bonding does not govern the work of adhesion between CNF and GO, but plays an important role for interfacial shear strength.